Lower risk of decompression sickness after recommendation of conservative decompression practices in divers with and without vascular right-to-left shunt - Klingmann, Christoph; Rathmann, Nils-Andreas; Hausmann, Daniel; Bruckner, Thomas; Kern, Rolf (Diving and hyperbaric medicine, 2012)
Introduction: A vascular right-to-left shunt (r/l shunt) is a well-known risk factor for the development of decompression sickness (DCS). No studies to date have examined whether divers with a history of DCS with or without a r/l shunt have a reduced risk of suffering recurrent DCS when diving more conservative dive profiles (CDP). Methods: Twenty-seven divers with a history of DCS recommended previously to dive more conservatively were included in this study and retrospectively interviewed by phone to determine the incidence of DCS recurrence.RESULTS: Twenty-seven divers performed 17,851 dives before examination in our department and 9,236 after recommendations for conservative diving. Mean follow up was 5.3 years (range 0-11 years). Thirty-eight events of DCS occurred in total, 34 before and four after recommendation of CDP. Four divers had a closure of their patent foramen ovale (PFO). A highly significant reduction of DCS risk was observed after recommendation of CDP for the whole group as well as for the sub-groups with or without a r/l shunt. A significant reduction of DCS risk in respect to r/l shunt size was also observed.DISCUSSION: This study indicates that recommendations to reduce nitrogen load after DCS appear to reduce the risk of developing subsequent DCS. This finding is independent of whether the divers have a r/l shunt or of shunt size. The risk of suffering recurrent DCS after recommendation for CDP is less than or equal to an unselected cohort of divers.Conclusion: Recommendation for CDP seems to significantly reduce the risk of recurrent DCS.
Gesehen am 24.10.2018